ผลของสารสกัดพืชสมุนไพรและระยะเวลาการแช่ในสารสกัดพืชสมุนไพรต่อคุณภาพของผลิตภัณฑ์มะละกอแก้วเสริมสารสกัดพืชสมุนไพร EFFECT OF HERBAL PLANT EXTRACTS AND IMMERSION TIMES ON THE QUALITY OF SWEET DEHYDRATED GREEN PAPAYA FORTIFIED WITH THE EXTRACTS - ร้องคำ, หทัยทิพย์; ดาจันทา, เกตุการ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This research was aimed to study the effect of two types of herbal plant extracts, including butterfly pea (Clitoria Ternatea L.) and safflower (Carthamus tinctorius L.), as well as immersion times (30, 60, and 90 min) of green papaya in each plant extracts on the quality of physical, chemical, total phenolic contents and antioxidant capacities of sweet dehydrated green papaya. The research data revealed that, the lightness (L*) value of sweet dehydrated green papaya fortified with butterfly pea and safflower extracts tend to decrease as the immersion time increased. Whereas, the value of total soluble solid were found to increase with immersion time increased. The immersion time did not affect to the hardness value of the sweet dehydrated green papaya fortified with both of herbal plant extracts products (p>0.05). For the antioxidant properties, increasing time of immersed green papaya in the extracts showed significant increasing of total phenolic contents, DPPH radical-scavenging capacities (DPPH) and ferric reducing antioxidant power (FRAP) (P≤0.05). The present study concluded that the highest antioxidant properties were found in the products immersed in the extract for 90 min, followed by the samples treated for 60 and 30 min, respectively. Furthermore, the sweet dehydrated green papaya fortified with butterfly pea extract showed higher content of total phenolic and antioxidant activities (DPPH and FRAP) than that found in the sample fortified with safflower extract. Therefore, sweet dehydrated green papaya fortified with butterfly pea and safflower extract products are a new healthy food product made from green papaya.